To What Extent Have The Attitudes of Senior Management in The UK Insurance Companies Developed in The Light of Changes in Genetics Technology in The Last Decade? - Haizel-Cobbina, Vera Kate (2007)
In 1984, a twenty-year international science project namely Human Genome Project (HGP) was initiated to map the overall genetic structure of the human species. The findings of HGP threw a new light into genetic tests, which attracted the interest of employers, bankers and insurers in most developed countries. Thus, genetic tests became a precondition for the attainment of certain benefits like bank loan, employment and insurance. As a result, a lot of pressure groups in different countries started condemning the use of genetic information by some service providers. The fear of many was a possible creation of uninsured 'underclass'. The outcry of stakeholders led to the enactment of legislations and voluntary agreements such as the moratorium in the U.K.